Analisis Akuntabilitas Lembaga Pendidikan Kontemporer - Arif Fiandi (Al-Tarbiyah : Jurnal Ilmu Pendidikan Islam, 2023)
The purpose of this study is to discuss and find out about the concept of accountability in contemporary educational institutions. This research method uses literature review, by studying from literary sources that are relevant to the material discussed. Accountability is the obligation to provide accountability for a mandate or responsibility assigned to related parties, especially the party providing the mandate. The application of accountability in educational institutions is a must to increase public trust in educational institutions. Forms of implementing accountability in contemporary educational institutions include: Decisions must be made in writing and available to every citizen who needs them, accuracy and completeness of information, explanation of policy objectives taken and communicated, feasibility and consistency, and dissemination of information regarding a decision. One of the accountability models applied in contemporary educational institutions is administrative accountability, which includes traditional accountability, managerial accountability, program accountability and process accountability.